Auswirkungen des gesetzlichen Mindestlohns – Bilanz nach fast vier Jahren - Jan Zilius; Oliver Bruttel (Wirtschaftsdienst, 2018)
Der gesetzliche Mindestlohn wurde zum 1. Januar 2015 eingeführt, nachdem zuvor die möglichen Auswirkungen kontrovers diskutiert wurden.1 Der Beitrag zieht auf Basis der inzwischen verfügbaren Daten und einer Vielzahl von Forschungsergebnissen Bilanz. In der Diskussion standen vor allem mögliche negative Beschäftigungseffekte im Vordergrund. Es hat sich aber gezeigt, dass auch andere Anpassungskanäle eine wichtige Rolle spielen. – – Germany did not establish a statutory minimum wage until 2015. Its introduction affected around 11 % of the workforce. Based on the German Minimum Wage Commission's second report, we provide a broad review of the measurable effects so far. The examined effects range from wage development, employment, unemployment and vacancies to welfare dependency and the risk of poverty to labour costs, productivity, prices, profi ts and the competitive environment. We also discuss issues of compliance in relation to the implementation of the new wage fl oor. JEL Classifi cation: J21, J31, J38,
Keywords: J21; J31; J38; K31; 330